Oxytocin signaling in pain: cellular, circuit, system, and behavioral levels - Poisbeau, Pierrick; Grinevich, Valéry; Charlet, Alexandre (Behavioral pharmacology of neuropeptides: Oxytocin, 2018)
Originally confined to the initiation of parturition and milk ejection after birth, the hypothalamic nonapeptide oxytocin (OT) is now recognized as a critical determinant of social behavior and emotional processing. It accounts for the modulation of sensory processing and pain perception as OT displays a potent analgesic effect mediated by OT receptors (OTRs) expressed in the peripheral and central nervous systems. In our chapter, we will first systemically analyze known efferent and afferent OT neuron projections, which form the anatomical basis for OT modulation of somatosensory and pain processing. Next, we will focus on the synergy of distinct types of OT neurons (e.g., magno- and parvocellular OT neurons) which efficiently control acute inflammatory pain perception. Finally, we will describe how OT signaling mechanisms in the spinal cord control nociception, as well as how OT is able to modulate emotional pain processing within the central amygdala. In the conclusions at the end of the chapter, we will formulate perspectives in the study of OT effects on pain anticipation and pain memory, as well as propose some reasons for the application of exogenous OT for the treatment of certain types of pain in human patients.